Rancang Bangun Sistem Monitoring Tempat Sampah Berbasis Internet of Things Menggunakan Node-Red - Kodar Udoyono; Ari Amabarwati (STMIK SUBANG, 2022)
The rapid development of development has not been matched by serious awareness of environmental impacts. Especially garbage. This is usually present as a risk for a city that moves to become a big city. A large population with a high growth rate results in an increase in the volume of waste. In addition, people's consumption patterns contribute to the emergence of increasingly diverse types of waste, including packaging waste which is dangerous and/or difficult to decompose by natural processes and can damage the surrounding environment. is very vital. Many cities in Indonesia in building Final Disposal Sites (TPA) do not pay attention to the standards for making TPA and pay attention to Environmental Impact Analysis (AMDAL). It is no doubt that many cases in big cities arise due to waste, both household waste and industrial waste because it is not treated and managed properly.